Pernikahan Semarga Bagi Masyarakat Lamaholot dalam Perspektif Hukum Islam - Hidayatullah Ratuloly; Muhammad Akil; Said Syarifuddin (Al-Tafaqquh: Journal of Islamic Law, 2021)
In the customary law of Lamaholot concerning the prohibition of marriages that are patrilineal in nature or draw a lineage from the father, it is called "Kakan Noon Aring" (brother and sister). The purpose of this research is to find out the views of the Lamaholot community regarding family marriages in Lamahala Jaya Village and how the sanctions are given if they have violated the legal provisions in Lamahala Jaya Village in an Islamic view. The results of this study indicate that the majority of the Lamaholot community still strongly adheres to the customary law governing marriage, which can only be carried out if the couple is of a different ethnicity, clan or clan. In Islamic law, it is forbidden to marry a mother, daughter, sister, mother, father or mother, grandchildren, nieces, breast-feeding women and siblings, parents-in-law, step-daughter, son-in-law and marrying two women who are sisters at the same time so that it is clear that there is no prohibition on clan marriage in Islamic law is (mubah).